Ontological Parsimony, Erosion, and Conservatism. (October 2016) - Metcalf, Thomas
Abstract: This article presents a novel argument against a common principle of parsimony in philosophy. First, it identifies a widely employed principle of positive ontological parsimony, according to which we should, ceteris paribus, prefer smaller ontologies to larger ontologies. Next, it shows how this principle is used as part of a strategy by which to argue for antirealist positions in many subfields of philosophy: the ockhamistic antirealist strategy . Third, it argues that this principle commits its adherents to an implausible epistemological thesis—the Eroding Ontology Thesis —according to which evidence for the existence of some entity is at least prima facie evidence against the existence of all other entities. Antirealists might decide to adopt a related position, ontological conservatism, according to which we should simply resist changing our ontology, but the article shows that it is independently unjustified. Therefore, it concludes, philosophers have good reason to cease employing one very common antirealist strategy.